Histological and Biochemical Parameters Follow-up in Experimental rats Administrated dexamethasone and Treated with Green Synthesis Titanium Dioxide Nanoparticles Using (Camillia sciences) Extracts - Nada abbas et al. (مجلة بغداد للعلوم)
In this study, Titanium Dioxide Nanoparticles were synthesized by an easy and eco-friendly technique (green synthesis) using green tea leaves (Camillia sinensis), Nanoparticles were analyzed using structural and optical analysis, the X-ray pattern showed that Titanium Dioxide NPs had a tetragonal structure with (Face Centered Tetragonal) FCT crystal structure, the UV-visible recorded an absorbance peak near 350 nm and calculated energy band gap was 3.5 eV, all measurements were proved the purity and Nano size of prepared Nanoparticles. Biochemical parameters evaluation also mentioned in this research, these analyzes showed that Titanium Dioxide nanoparticles in particular dose (50 mg/kg) have the ability to reduce blood glucose levels, improve liver functions and recover lipid levels in the animals body, and lastly, histological pancreatic parts were submitted to observe changes that occurred after dexamethasone and nanoparticles were injected.